ANALISIS PEMUTUSAN HUBUNGAN KERJA DENGAN ALASAN DISHARMONI (STUDI KASUS PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR 121/PDT.SUS-PHI/2018/PN.BDG Juncto PUTUSAN MAHKAMAHi AGUNG NOMOR1942 K/PDT.SUS-PHI/2018) - Luxena Gabriella; Stanislaus Atalim (Jurnal Hukum Adigama, 2019)
This different opinion of termination sometime causing industrial relation dispute. The increasing reasons of employment termination constantly do harm for the workers without considering the loss that they may experience. How the Judge consider to make decision of termination with disharmony as the reason as stated in Constitution No. 13 Year 2003 about Employment? The research types that being used was a Normative Research. There are various reason in an employment termination. Dispute in Employment termination is a dispute of how employment relation ends. Terminating an employment relation must be accompanied by detailed and described as stated in Constitution No. 13 year 2003 about Employment. The Provision about arrangements for employment termination set out in article 150 until 171 Constitution No. 13 Year 2003 about Employment. Issues in this case is that PT Sari Gemilang didn’t described in detailed their reason why they terminated their workers. In the decisions of the Supreme Court didn’t consider Article 57 paragraph (2), Article 59 Paragraph (4), and Article 59 Paragraph (7) also Article 151 Paragraph (3) and Article 155 Paragraph (1) Constitution No. 13 Year 2003. Judge only considered that the relation between Company and Workers are disharmony. Disharmony is a situation, not a reason for termination. Panel of judges of the supreme court didn’t see there are reason for termination or not. There is uncertainty on the termination fee and the calculation that need to be paid by the employer due to disharmony.